Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Anggota Unit SPKT (Sentra Pelayanan Kepolisian Terpadu) Polres Merangin dengan Motivasi Kerja sebagai Variabel Intervening - Anggara Anggara; Almasdi Almasdi (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to see the effect of 1). The influence of the work environment on the work motivation of the members of the SPKT Polres Merangin unit. 2). The effect of work discipline on the work motivation of the members of the SPKT Polres Merangin unit. 3). The effect of work motivation on the performance of the members of the Kerinci Police SPKT unit. 4). The influence of the work environment on the performance of the members of the SPKT Polres Merangin. 5). The effect of work discipline on the performance of the members of the Kerinci Police SPKT unit. 6). The influence of the work environment on the performance of the members of the Kerinci Police SPKT unit with work motivation as an intervening variable. 7). The effect of work discipline on the performance of the members of the SPKT Polres Merangin unit with work motivation as an intervening variable. The population in this study were all 42 members of the SPKT Polres Merangin Unit. And the technique of determining the number of samples taken as respondents using total sampling. The results of this study indicate that the work environment and work discipline have a significant effect on the work motivation of the members of the SPKT unit at the Kerinci Police. In addition, the work environment, work discipline and motivation also have a significant effect on the performance of the members of the SPKT unit at the Kerinci Police.